2021
DOI: 10.1007/jhep05(2021)129
|View full text |Cite
|
Sign up to set email alerts
|

Dark matter in the type Ib seesaw model

Abstract: We consider a minimal type Ib seesaw model where the effective neutrino mass operator involves two different Higgs doublets, and the two right-handed neutrinos form a heavy Dirac mass. We propose a minimal dark matter extension of this model, in which the Dirac heavy neutrino is coupled to a dark Dirac fermion and a dark complex scalar field, both charged under a discrete Z2 symmetry, where the lighter of the two is a dark matter candidate. Focussing on the fermionic dark matter case, we explore the parameter … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 141 publications
0
31
0
Order By: Relevance
“…Recently a new version of the type I seesaw mechanism, named as the type Ib seesaw mechanism [56], that can be just as testable as the low scale seesaw models above has been proposed, with the light neutrino masses originating from a new type of Weinberg operator involving two Higgs doublets and a Dirac heavy neutrino. It has been shown that the model cannot only be extended to include dark matter via a neutrino portal [57] but can also produce baryon asymmetry in a variant version [58]. However in this model, as in many such models, both the type Ib seesaw model itself and the inclusion of dark matter via a neutrino portal requires additional imposed discrete symmetries whose origin is not explained.…”
Section: Jhep12(2021)121mentioning
confidence: 99%
See 3 more Smart Citations
“…Recently a new version of the type I seesaw mechanism, named as the type Ib seesaw mechanism [56], that can be just as testable as the low scale seesaw models above has been proposed, with the light neutrino masses originating from a new type of Weinberg operator involving two Higgs doublets and a Dirac heavy neutrino. It has been shown that the model cannot only be extended to include dark matter via a neutrino portal [57] but can also produce baryon asymmetry in a variant version [58]. However in this model, as in many such models, both the type Ib seesaw model itself and the inclusion of dark matter via a neutrino portal requires additional imposed discrete symmetries whose origin is not explained.…”
Section: Jhep12(2021)121mentioning
confidence: 99%
“…The charges of the fields in the model are summarised in table 1. The U (1) gauge symmetry, rather than any discrete Z 3 or Z 4 symmetries [57,58], is responsible for making the two Higgs doublets distinguishable and ensuring the type Ib seesaw structure. However, the U(1) symmetry does not completely take over the function of the discrete symmetries.…”
Section: Extension Of the Minimal Type Ib Seesaw Model As An Effective Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…We show that this choice is apt for the freeze-in mechanism. The neutrino sector on the other hand, is far more model dependent and could also lead to freeze-in mechanisms for certain models (see for example, [32,33]). We also address the issue of stability for charged lepton flavored DM and show that in the absence of total lepton number violating interactions, they can be absolutely stable.…”
Section: Introductionmentioning
confidence: 99%